2021
DOI: 10.3389/fimmu.2021.771826
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum Alleviates Enterotoxigenic Escherichia coli K88-Induced Oxidative Damage Through Regulating the p62-Keap1-Nrf2 Signaling Pathway and Remodeling the Cecal Microbial Community

Abstract: Clostridium butyricum (CB) can enhance antioxidant capacity and alleviate oxidative damage, but the molecular mechanism by which this occurs remains unclear. This study used enterotoxigenic Escherichia coli (ETEC) K88 as a pathogenic model, and the p62-Keap1-Nrf2 signaling pathway and intestinal microbiota as the starting point to explore the mechanism through which CB alleviates oxidative damage. After pretreatment with CB for 15 d, mice were challenged with ETEC K88 for 24 h. The results suggest that CB pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 60 publications
(74 reference statements)
2
25
0
Order By: Relevance
“…CB is reported to have the ability to protect the intestinal barrier through the activation of the Akt/mTOR signaling pathway (22). Research also revealed the mechanisms of CB in alleviating Enterotoxigenic Escherichia K88-induced oxidative damage (23). It is undeniable that CB has enormous potential in the treatment of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…CB is reported to have the ability to protect the intestinal barrier through the activation of the Akt/mTOR signaling pathway (22). Research also revealed the mechanisms of CB in alleviating Enterotoxigenic Escherichia K88-induced oxidative damage (23). It is undeniable that CB has enormous potential in the treatment of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, it is considered as pathogenic bacteria ( 27 ) that is linked to a polymicrobial infection in clinical cases ( 28 ). However, the genus Terrisporobacter is also closely related to SCFA contents and oxidative indicators ( 29 ) and plays a key role in degrading organic matter ( 28 ). The Succinivibrio was also enriched in E2, which is regarded as a double-edged sword, not only involved in the accumulation of anti-inflammatory cytokines and viral inhibitors but also induced the inflammatory responses in the gut ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our intestinal histology also found that there was inflammatory damage to the intestinal barrier. A certain amount of Clostridium butyricum can reduce oxidative damage and enhance the antioxidant capacity of mouse pathogenic models treated with toxin producing Escherichia coli , by activating the p62-Keap1-Nrf2 signal pathway and remodeling the intestinal microbial community [ 50 ]. We observed that the relative abundance of the dominant species members of Firmicutes in FIS was lower in Dia, consistent with previous finding on the gut microbiota of piglets with diarrhea [ 12 ].…”
Section: Discussionmentioning
confidence: 99%